Factor VII deficiency – an enigma; clinicohematological profile in 12 cases. Issue 1 (1st January 2019) - Tripathi, Preeti; Mishra, Priyanka; Ranjan, Ravi; Tyagi, Seema; Seth, Tulika; Saxena, Renu
ABSTRACT: Objective : Factor VII deficiency is the commonest of the rare bleeding disorders with limited knowledge on clinical profile. The objective of this study was to study the prevalence and clinico-hematological profile of factor VII-deficient patients. Methods: It is a retrospective observational study of probable inherited factor VII deficiency covering 18 months. Their clinical profile, family history, investigation and treatment records were studied in detail. Results: The study group comprised of total 12 factor VII deficiency cases with mean age of 17.5 years of onset of symptoms. The commonest symptom was menorrhagia (41.6%) followed by epistaxis (25%) and easy bruisability (16.6%). These 12 patients when categorized according to bleeding severity: severe bleeding – 2, moderate bleeding – 3, mild bleeding – 6 and asymptomatic – 1. All cases had prolonged prothrombin time (PT) with mean PT of 35.4 seconds (range 18–50 seconds) and mean prolongation of PT from upper limit of normal – 19.4 seconds (range 2–34 seconds). Factor VII levels ranged from < 1–40% in these patients. Clinical symptoms were not in concordance with factor levels. Of 12 patients, required treatment other than local measures. Discussion and Conclusion: Inherited factor VII deficiency is the commonest autosomally inherited factor deficiency with marked variation in the age of presentation and clinical symptoms. The laboratory results in form of PT and factor VII levels do not correlate with the severity of clinical presentation. A comprehensive evaluation to exclude acquired causes of factor VII deficiency, e.g. obesity, liver diseases, vitamin K deficiency and acquired inhibitors is required before labeling it as inherited in the absence of family history and molecular studies.